Digital marketing strategy for adventure tour packages on the Trekking Rinjani website with an online marketing model approach - Surayyal Hizmi; Ni Nengah Ayu Trisna Puspawati (Universitas Merdeka Malang, 2023)
Trekking Rinjani is a travel agent that has been established for a long time with a market focus on adventure tour packages via the website. In recent times, sales of adventure tour packages on this type of travel have decreased, so there is a need for appropriate strategies as reference and evaluation material in competing and increasing the number of customers, especially at low sessions. The study was conducted on the marketing strategy by reviewing strengths, weaknesses, opportunities and threats aspects of Trekking Rinjani with consideration of the 5C (Customer, Creative Content, Communication, Consistency and Control) aspects of the Online Marketing Model, where all data is collected through an interview process and secondary data analysis from Google Analyst. The data is then aggregated and classified based on internal and external factors through a SWOT analysis. Based on the SWOT analysis, it was found that Trekking Rinjani has to improve service and content quality to increase the enthusiasm of the visitors on the website in enjoying the content as well as to improve customer trust. In addition, the quality of the website display and minimizing errors in the website system should be conducted.